A Morphological Error Analysis of Students’ Written Reports on Indonesia’s 2014 Presidential Election - Soraya Grabiella Dinamika; Elitaria B.A. Siregar (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis study, conducted at the Department of English Literature of Universitas Sumatera Utara (USU), aimed to investigate the morphological errors made by university students in their report texts on Indonesia’s Presidential Election in 2014. The objectives of this qualitative and descriptive study were to: a) find out the most predominant morphological errors made by the students; b) investigate the sources causing the errors; and c) suggest appropriate remediation for identified morphological errors. In analyzing the data, the Error Analysis theory, espoused by Gass and Selinker (2008), was applied as it provides six systematic procedures in overcoming L2 learning errors. Results of the analysis revealed that the students respectively made significant morphological errors in: a) the use of derivational morphemes with 46 errors (51%); b) the use of inflectional morphemes with 43 errors (47%); and c) the use of affixes with two errors (2%). The morphological error made by the students was caused by two primary sources, the interlanguage and intralanguage errors. To address these problematic areas, the researchers have suggested several pedagogical remediations to follow up.ABSTRAKPenelitian ini bertujuan untuk mengetahui kesalahan morfologi yang dibuat oleh mahasiswa Departemen Sastra Inggris Universitas Sumatera Utara, dalam teks laporan yang mereka tulis tentang Pemilihan Presiden Tahun 2014. Selain itu, penelitian ini bertujuan untuk; a) mencari tahu jenis kesalahan morfologi apa yang paling banyak terjadi; b) mencari tahu sumber penyebab kesalahan; dan c) memberikan langkah-langkah yang sesuai untuk mengatasi kesalahan morfologi. Dalam menganalisis data, teori yang digunakan adalah Teori Analisis Kesalahan yang digubah oleh Gass & Selinker pada tahun 2008, karena teori ini memuat enam prosedur lengkap dalam menangani masalah kesalahan pembelajaran bahasa kedua. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Hasil analisis data mengemukakan bahwa kesalahan yang paling banyak terjadi dalam penggunaan morfem derivasi dengan jumlah 46 kesalahan (51%), diikuti oleh penggunaan morfem infleksional dengan jumlah 43 kesalahan (47%), dan yang paling sedikit adalah penggunaan imbuhan dengan jumlah 2 kesalahan (2%). Ada dua penyebab terjadinya kesalahan morfologi, yaitu kesalahan intrabahasa dan kesalahan interbahasa. Selanjutnya, peneliti menyarankan sejumlah langkah remediasi pedagogik untuk mengatasi kesalahan morfologi. How to Cite: Dinamika, S. G., Siregar, E. B.A.. (2020). A Morphological Error Analysis of Students’ Written Reports on Indonesia’s 2014 Presidential Election. IJEE (Indonesian Journal of English Education), 7(1), 85-94. doi:10.15408/ijee.v7i1.16978